Effectiveness and safety of Qingfei Dayuan granules for treating influenza and upper respiratory tract infections manifested by the pulmonary heat-toxin syndrome: A multicenter, randomized, double-blind, placebo-controlled trial - Li, Weinan; Xie, Lihan; Zhu, Xiaoyun; Yang, Yi; Wang, Linqun; Yang, Min; Li, Hengfei; Li, Xucheng; Yan, Guangjun; Wu, Xiongfei; Zhao, Weijun; Zhang, Jilong; et al. (Frontiers in Pharmacology, 2023)
Background: Patients diagnosed with influenza and upper respiratory tract infection（URTI） have such similar clinical manifestations and biochemical indicators as low detection rate of viral pathogens, mixed infection of diverse respiratory viruses and difficult targeted antiviral treatment in the early stage. According to the treatment principle of “Same Treatment for Different Diseases”, in traditional Chinese medicine, different diseases having the same clinical symptoms can be treated with the same medicines. Qingfei Dayuan granules (QFDY) (Approval number by medical institutions in Hubei Province: Z20200003), one sort of Chinese herbal preparation included in the Diagnosis and Treatment Protocol of TCM for COVID-19 of Hubei Province by the health authorities of Hubei Province in 2021, is recommended for patients suffering from COVID-19 with symptoms of fever, cough, fatigue, etc. Materials and methods: QFDY for influenza and URTI with heat-toxin attacking lung syndrome trial is a multi-center, randomized, double-blind, placebo-controlled superiority clinical trial that enrolls patients from eight 3A-grade hospitals in five major cities of Hubei Province in China. 220 eligible patients would be randomized to receive either 15 g QFDY or placebo three times a day for 5 days. The primary outcome was the complete fever relief time. The secondary outcomes were efficacy evaluation of TCM syndromes, scores of TCM syndromes, curing rate of each singular symptom. Results: Compared to placebo group, the complete fever relief time of the control group was shorter (P ≤ 0.001), and after 3 days of treatment, the clinical recovery rate and the curing rate of coughing, stuffy and running nose and sneezing of the control group was higher (P < 0.05) in the QFDY group. There were no significant differences between the two groups in scores of TCM syndromes, incidence of complications and developing into severe conditions, combined medication and laboratory tests (P > 0.05). Conclusion:QFDY is an effective and safe treatment against influenza and URTI with heat-toxin attacking lung syndrome in shortening complete fever relief time, and accelerating clinical recovery as well as alleviating of symptoms like cough, stuffy and running nose and sneeze in the treatment process.